Do Simplified Text Can Improve Students’ Reading Comprehension in Narrative Text?: A Classroom Action Research Perspective - Suwondo Suwondo; Syaifullah Syaifullah (Utamax : Journal of Ultimate Research and Trends in Education, 2019)
This research was based on the researcher's preliminary study which found that the students could not comprehend the meaning of texts in their textbook. This Classroom Action Research (CAR) aims to improve the students’ reading comprehension in narrative text through simplified text at grade VIII of SMP Budhi Luhur Pekanbaru. The research was administered to the second year students of SMP Budhi Luhur Pekanbaru. The total population was 34 students. After analyzing the data, the researcher found a significant effect of simplified text toward reading at the second-year SMP Budhi Luhur Pekanbaru students, where the average score from the based score was 58. It increased to 66 at the end of the cycle I. Finally, the average score of cycle II was 75. So it can be concluded that simplified text can increase the students' reading skill at grade VIII SMP Budhi Luhur Pekanbaru